Information Sharing and Strategic Supplier Partnership in Supply Chain Management: A Study on Pharmaceutical Companies of Pakistan - Khan, Ambreen; Siddiqui, Danish Ahmed (Asian Business Review, 2018)
The aim of this paper is to distinguish the relationship between different components of supply chain management (SCM) and its impact on the performance of pharmaceutical manufacturing firms in Pakistan. Data has been gathered from 35 pharmaceutical companies located in the big cities of Pakistan. Self-reported questionnaires were used to collect data from the managerial level people working in different pharmaceutical companies of Pakistan. The result indicates that strategic supplier partnership, level of information sharing and quality of information sharing significantly correlates with the performance of manufacturing pharmaceutical firms. The current study will prove fruitful for the organization in improving their performance by implementing concepts of SCM within their companies. The study explored that all independent variables significantly predicted the performance of the firm. Strategic supplier partnerships, quality of information sharing have a positive effect on the performance of pharmaceutical companies whereas the level of information sharing has a negative impact on performance. The findings provide the evidence for previous literature. Results are helpful to policy makers and management to integrate the concepts within the organization to increase the performance of the firm and to win competitive advantage.